Genetic polymorphisms of drug-metabolizing enzymes and anti-TB drug-induced hepatitis. (November 2009) - Kim, Sang-Heon; Kim, Sang-Hoon; Bahn, Joon-Woo; Kim, Yoon-Keun; Chang, Yoon-Seok; Shin, Eun-Soon; Kim, Youn-Seup; Park, Jae-Seuk; Kim, Bo-Hyung; Jang, In-Jin; Song, Junghan; Kim, Seung-Hyun; et al.
Aims: Although some genetic risk factors have been reported for the development of hepatitis due to anti-TB drugs, an extensive candidate gene approach evaluating drug-metabolizing enzymes has not been attempted. This study aimed to investigate the association of genetic polymorphisms in drug-metabolizing enzymes with anti-TB drug-induced hepatitis.Materials & methods: We compared genotype distributions of tagging SNPs in promoter, exons and haplotypes in seven drug-metabolizing enzyme genes ( CYP2C9, CYP2C19, CYP2D6, CYP2E1, NAT2, UGT1A1 and UGT1A3 ) between 67 cases and 159 controls.Results: Among four tagging SNPs of N -acetyltransferase 2 ( NAT2 ), -9796T>A in promoter and R197Q were significantly associated (p = 0.0016 and p = 0.0007, respectively). NAT2 haplotype 2 [A-A-A-G] carrying A allele of -9796T>A and A allele of R197Q showed significant association (p = 0.0004). However, there was no significant association between genotypes of other enzyme-metabolizing genes and anti-TB drug-induced hepatitis. The constructs containing -9796A of NAT2 showed significantly lower luciferase activity (p < 0.01), suggesting decreased expression of NAT2 . The variant alleles and haplotype 2 showed significantly higher peak serum levels of isoniazid, lower acetyl isoniazid:isoniazid ratio and lower isoniazid clearance compared with wild-types.Conclusion: These findings suggest that genetic variants in the promoter and exons of NAT2 increase the risk of anti-TB drug-induced hepatitis by modifying acetylation phenotypes and/or gene expression of NAT2, and there is no essential role for genetic mutation of the other metabolizing enzymes in the development of this adverse reaction.